2009
DOI: 10.1371/journal.pone.0006118
|View full text |Cite
|
Sign up to set email alerts
|

Influenza-Like Illness Sentinel Surveillance in Peru

Abstract: BackgroundAcute respiratory illnesses and influenza-like illnesses (ILI) are a significant source of morbidity and mortality worldwide. Despite the public health importance, little is known about the etiology of these acute respiratory illnesses in many regions of South America. In 2006, the Peruvian Ministry of Health (MoH) and the US Naval Medical Research Center Detachment (NMRCD) initiated a collaboration to characterize the viral agents associated with ILI and to describe the clinical and epidemiological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
116
4
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(141 citation statements)
references
References 11 publications
17
116
4
4
Order By: Relevance
“…Our levels of positive detection appeared to be in accordance with those obtained in these two studies. However, our incidence data appeared to be higher than those obtained in the Peruvian study (68.4% versus 43%; P Ͻ 0.001) (22); this could be explained by the larger number of common and newly discovered respiratory pathogens potentially detectable by the RT-PCR DNA microarray detection systems as well as by the high sensitivity of this detection technology, allowing limits of detection ranging from 10 to 100 copies of viral genomes per amplification tube. Interestingly, in the present study, influenza A/H1N1v virus was detected in only 30 (31%) of the 95 tested patients, and influenza A/H3N2 virus was detected in only 2 (2.1%) of the 95 tested patients (Fig.…”
Section: Discussioncontrasting
confidence: 82%
See 3 more Smart Citations
“…Our levels of positive detection appeared to be in accordance with those obtained in these two studies. However, our incidence data appeared to be higher than those obtained in the Peruvian study (68.4% versus 43%; P Ͻ 0.001) (22); this could be explained by the larger number of common and newly discovered respiratory pathogens potentially detectable by the RT-PCR DNA microarray detection systems as well as by the high sensitivity of this detection technology, allowing limits of detection ranging from 10 to 100 copies of viral genomes per amplification tube. Interestingly, in the present study, influenza A/H1N1v virus was detected in only 30 (31%) of the 95 tested patients, and influenza A/H3N2 virus was detected in only 2 (2.1%) of the 95 tested patients (Fig.…”
Section: Discussioncontrasting
confidence: 82%
“…Numerous previous studies detected the presence of influenza viruses in the respiratory tracts of ILI patients by use of real-time RT-PCR systems during 2007 to 2008 (18,30,41,42). These studies reported levels of positive influenza A virus seasonal strain detection ranging from 25% in Peru to 40% in Greece (18,22). Our level of influenza A virus detection (33.1%) appears to be in agreement with previous published worldwide studies (17,22,30,41,42 Interestingly, the combination of two RT-PCR DNA microarray systems allowed us to detect not only influenza A virus strains but also 17 other common or newly discovered respiratory viruses in the same sample.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…América del Sur presenta diversos tipos de circulación de los virus gripales, en los países templados, la circulación es estacional y limitada a la estación invernal mientras que en los países con clima tropical, los virus circulan durante todo el año, pero con uno o dos picos de actividad que coinciden con las épocas de lluvia. En algunos países existen diferencias en la estacionalidad de la infl uenza [41][42][43][44] . La incidencia anual de tuberculosis es muy variable entre los países de la región 45 .…”
Section: Enfermedades De Transmisión Interhumana Y Por Aerosolesunclassified